Equivalence in the Translation of Joko Pinurboâ€™s â€œTuhan Datang Malam Iniâ€ into â€œGod Came Tonightâ€ - Hayuwardhani, Aurelia Reza (Indonesian Journal of English Language Studies (IJELS), 2020)
The paper presents an analysis of Joko Pinurboâ€™s â€œTuhan Datang Malam Iniâ€ translated intoâ€œGod Came Tonightâ€. In this paper, the translation of the original version is seen closely tosee its equivalence strategies, referring to Nidaâ€™s framework, applied to the production of thetranslation. The equivalence explained in the discussion covers both formal and dynamic. Thediscussion in the paper leads to three major conclusions, namely: (1) figurativeness in a poemcan be preserved by the help of formal equivalence, (2) the type of equivalence depends onhow far translators bring it to the translation, and (3) translators need to have broadknowledge to supply their work in translation, especially in that of poetry.Keywords: Joko Pinurbo, Nidaâ€™s framework, formal, and dynamic equivalence.